Penerapan Model Kooperatif Tipe Jigsaw Untuk Meningkatkan Hasil Belajar Matematika Kelas IV SD - Agusti, Silvia; Astimar, Nelly (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This study aims to describe the application of the Jigsaw Cooperative model to improve mathematics learning outcomes in circumference and area of plane figure in fourth grade of Elementary School. The type of this research is Classroom Action Research (CAR) using qualitative and quantitative approaches. The research subjects were teachers and 30 students in the fourth grade of elementary school 15 Koto Lalang. The results of this study showed an improvement the outcomes of mathematics learning. The result of the lesson plan in the first cycle was 82.14% to 94.36% in the second cycle. The result of observation for teacher and student aspects in the first cycle was 77.78% to 90.28% in the second cycle. The assessment of mathematical learning outcomes of students in the first cycle was about  71.51 to 83.07  in the second cycle.